2016
DOI: 10.1177/0954408916646139
|View full text |Cite
|
Sign up to set email alerts
|

Shape effect of nanosize particles in unsteady mixed convection flow of nanofluid over disk with entropy generation

Abstract: The aim of this paper is to study the different shapes of nanoparticles on mixed convective steady flow over a rotating disk. For nanofluid, the copper nanoparticles of disk, cylindrical, and spherical shapes of different sizes and water as base fluid are considered. The physical problem is first modeled and then the governing equations are transformed into nonlinear ordinary differential equations. These equations are dimensionless using geometrical and physical flowfielddependent parameters and solved analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 21 publications
0
46
0
Order By: Relevance
“…The published work is incomplete, though for both of these physical parameter there exist numerous industrial and mechanical applications. The few other investigations in this direction were made by Ellahi et al [37], Akbar et al [38,39], Shehzad et al [40], and Zeeshan et al [41].…”
Section: Introductionmentioning
confidence: 97%
“…The published work is incomplete, though for both of these physical parameter there exist numerous industrial and mechanical applications. The few other investigations in this direction were made by Ellahi et al [37], Akbar et al [38,39], Shehzad et al [40], and Zeeshan et al [41].…”
Section: Introductionmentioning
confidence: 97%
“…They found that entropy generation enhances due to the influence of all the physical parameters. Some more pertinent studies on this topic can be found in references [23][24][25]. According to the best of our knowledge, entropy generation on viscous nanofluid flow through a horizontal Riga plate has not been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…Let us consider the following non-dimensional quantities With the help of Oberbeck-Boussinesq approximation, let us consider that nanoparticle is dilute, and then the boundary layer equations for continuity, linear momentum, thermal energy and concentration equation can be written as [24] …”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Ellahi et al studied Nanofluid over different phenomena mentioned in [13][14][15][16][17]. A detailed data on thin film Williamson Nanofluid Flow with Varying Viscosity and Thermal Conductivity on a Time-Dependent Stretching Sheet is given by Khan et al [18].…”
Section: Introductionmentioning
confidence: 99%